IMPACT OF BEHAVIORAL ACTIVATION ON COMORBID DEPRESSION AND TYPE 2 DIABETES IN LOW-INCOME ADULTS. (20th December 2022) - Griffith, Christopher; Feliciano, Leilani
Abstract: Older age is a significant risk factor for type 2 diabetes mellitus (T2DM), and depression risk increases with comorbid illnesses such as T2DM. Older adults with depression have increased risk of developing somatic symptoms and decreased interest in activities, which impacts diabetes self-care. This makes depression an important target for treatment alongside T2DM. Behavioral activation (BA) is a therapeutic intervention shown to be effective in the treatment of moderate to severe depression. The current study examined the utility of brief BA treatment (once weekly for 4 weeks) across older adults aged 60-80, middle-aged adults aged 45-59, and younger adults aged 18-44. Fifty-six adults with diabetes participated in an in-home diabetes management program with BA to treat depression in low-income adults. Participants completed weekly measures of well-being and depressive symptoms. Two mixed-subjects analyses of variance (3 x 2 ANOVAs) found that BA was significantly effective at improving subjective well-being, F (1, 53) = 38.24, p < .001, ηp2 = .42, and reducing depressive symptoms, F (1, 38) = 27.25, p < .001, ηp2 = .42, but found no interaction effects between either age group and well-being or depressive symptoms (p = .173 and .302, respectively). Results indicate that BA is effective for treating depression in adults with comorbid T2DM regardless of age, making it a useful therapeutic tool for both the high number of older adults with T2DM and their younger counterparts. Further research should examine other outcomes (diabetes management) to evaluate the full extent of BA's effectiveness.